Conduction system pacing in paediatric patients: a single centre experience. (19th May 2022) - Zizek, D; Topalovic, M; Stublar, J; Mrak, M; Jan, M; Weiss, M
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Paediatric patients with conduction abnormalities are generally exposed to life-long dyssynchronous pacing from a very early age. Thus, preservation of cardiac function during chronic ventricular pacing is important. Conduction system pacing (CSP) with His bundle pacing (HBP) or left bundle branch pacing (LBBP) is an alternative method to standard right ventricular (RV) pacing that may preserve physiological ventricular activation and avoid potential pacing-induced cardiomyopathy (1). However, data on feasibility and safety of various CSP approaches in paediatric patients with or without congenital heart disease (CHD) is scarce and mainly relies on case studies (2-4). Purpose: To assess feasibility and outcomes of different CSP techniques in paediatric patients. Methods: Consecutive paediatric patients in whom CSP was attempted in our centre between November 2019 and December 2021 were analysed. Acute implant success rate, complications, fluoroscopy times, and CSP pacing parameters during follow-up were assessed. To reduce radiation exposure, minimal fluoroscopy technique with three-dimensional (3D) electro-anatomical mapping (EAM) was also used in some cases. Geometry of right atrium and RV, along with mapping of His signal for HBP and potential LBBP sites in the RV septum were created using a decapolar catheter from the right femoral vein. Once relevant anatomy was obtained, HBP or LBBP was attempted using commercially available CSP tools. The pacing lead tip was visualised using the 3D EAM system. Transient fluoroscopy was used only for perpendicular placement of the sheath to the RV septum during LBBP, sheath removal, lead loop assessment to allow linear growth, and atrial lead placement. Results: Six patients (100% female, age 9.3 ± 3.9 years, weight 41.8 ± 22.9 kg, baseline QRS 111.5 ± 6.3ms, CHD 50%, previous device 33%) with congenital complete AV block received CSP. One patient received HBP and 5 LBBP. The procedure was acutely successful in all patients (100%), pacing thresholds were low (0.56 ± 0.18V at 0.5ms) and there were no perioperative complications. During mean follow-up of 11.8 ± 7.8 months pacing parameters remained stable. However, significant rise of the pacing threshold (> 2.5V) was registered in the HBP patient, in whom lead revision was performed. Three-dimensional EAM was utilised in 3 patients (1 HBP, 2 LBBP). The use of minimal fluoroscopy technique with 3D EAM reduced fluoroscopy time (4.0, 3.2, 4.5 min vs. 9.5, 11.0, 8.0 min) without increasing procedural time (80, 70, 50 min vs. 110, 60, 75 min) compared to standard fluoroscopy technique. Conclusion: Conduction system pacing is feasible and safe in paediatric patients with or without CHD. Additional utilisation of 3D EAM could reduce radiation exposure, without increasing procedural time. Future long-term studies should be considered to provide the ground for wider clinical adoption of CSP in paediatric population.